S130 Tnfα Driven Car Phosphorylation Promotes Trans Epithelial Migration Of Leukocytes. (10th November 2014) - Hicks, AP; Morton, P; Noble, A; Raynor, E; Parsons, M; Santis, G
Abstract : Transepithelial migration (TEpM) of leukocytes during the inflammatory process requires engagement with receptors expressed on the basolateral surface of the epithelium. One such receptor is Coxsackie and Adenovirus Receptor (CAR) which binds to Junction Adhesion Molecule – L (JAM-L) on leukocytes during TEpM. Here we provide the first evidence that TEpM of THP1 cells requires, and is controlled by phosphorylation of the cytoplasmic tail of CAR. Our in-vitro data shows that these leukocyte cells can adhere to an epithelial layer but where the cytoplasmic tail of CAR is prevented from undergoing phosphorylation the leukocytes are unable to transmigrate. Furthermore we show that this CAR phosphorylation step is driven by TNFα signalling via a TNFR1-PI3K-PKCδ dependent signalling pathway. Interestingly our work demonstrates that THP1 cells can secrete TNFα thereby activating the CAR phosphorylation pathway leading to TEpM without addition of exogenous TNFα but where TNFα is added this process is augmented. We also use a mouse model to confirm that CAR phosphorylation in response to inflammatory stimuli occurs in-vivo. Both acute (a 24 h inhaled TNFα challenge) and chronic (a 34 day ovalbumin challenge) inflammatory conditions are studied. Using confocal microscopy techniques we show that the cytoplasmic tail of CAR is phosphorylated. Specifically this is seen at the cell membrane of epithelial cells of bronchioles with associated inflammatory cells in the interstitium. Taken together these data describe a novel method for the control of TEpM by transmigrating leukocytes that can also be heightened by the presence of pro-inflammatory cytokines during inflammation. This provides a novel target for controlling inflammation at the epithelium, a key component of the pathogenesis of many diseases including asthma.